Forensic Accounting Skills and the Effective Identification in Money Laundering Activities – Transaction Monitoring Perspective - HASHIM, FARAH HAZWANI MOHAMMAD; ZAWAWI, SITI NOOR HAYATI MOHAMED; JUSOH, FATMAWATI; RASHID, NORFADZILAH (The journal of contemporary issues in business and government, 2021)
This research examined the relationship between forensic accounting skills and the identification of money laundering activities from the perspective of transaction monitoring. The forensic accounting skills is defined to consist of skills in auditing, investigative and critical thinking. The descriptive statistic indicates that the analysts rank investigative skills as the most important skills. The multiple regression analysis on 134 data collected from the transaction monitoring analysts showed that the investigative and critical thinking skills were medium to highly correlated with the identification of money laundering activities. These findings provide valuable insight and guidance to educators, practitioners, and other related parties that they have to give emphasise on these skills such as by providing training to keep the transaction monitoring analysts of the banking institutions updated with the new developments on investigative skills and enhance on the critical thinking skills for effective identification of money laundering activities.